Implementasi Kebijakan Program Kartu Tani Untuk Distribusi Pupuk Bersubsidi Di Kecamatan Pakisjaya Kabupaten Karawang Tahun 2021 - Riki Riki; Abdal Abdal; Wawan Setiawan Abdillah (PT WIM Solusi Prima, 2022)
The farmer card progranation policy is one of the government's efforts to keep the distribution of subsidized fertilizers on target. The problems of implementing the Farmer Card include the use of farmer cards that have not been optimally carried out by farmers, it needs to take a longer time in redeeming subsidized fertilizers because the EDC system is complicated and sometimes often experiences errors. Another problem is the facilities and infrastructure that still need to be improved. The purpose of this study was to see the distribution of subsidized fertilizers from the implementation of the farmer card program policy in Pakisjaya District. In this case, the researcher conducts an analysis of policy implementation according to Purwanto (2015) where there are seven indicators that can be used to see the performance of policy implementation, namely: Access, Scope, Frequency, Bias, Accuracy of services, Accountability and Suitability of programs with needs. The method used is a qualitative research method with a descriptive approach. Data collection was carried out by interview, observation, documentation and triangulation/combined. The results showed that from seven implementation performance indicators, the Pakisjaya District Agricultural Extension Center has carried out the farmer card program quite well. This can be seen from the distribution of subsidized fertilizers has been evenly distributed to almost 100%, although the distribution of farmer cards has not been 100% because they have to go through such a complicated bureaucracy. However, it is not a barrier, the process of distributing subsidized fertilizers can still be done because farmers have been registered with the RDKK. Kebijakan progran kartu tani merupakan salah satu upaya pemerintah untuk menjaga agar pendistribusian pupuk bersubsidi tepat sasaran. Masalah dari penerapan Kartu Tani diantaranya penggunaan kartu tani yang belum maksimal dilakukan oleh para petani, perlu membutuhkan waktu yang lebih lama dalam penebusan pupuk bersubsidi karena sistem EDC yang rumit dan terkadang sering mengalami eror. Masalah lain yakni sarana dan prasarana yang masih perlu dilakukan pembenahan. Tujuan penelitian ini adalah untuk melihat distribusi pupuk bersubsidi dari implementasi kebijakan program kartu tani di Kecamatan Pakisjaya. Dalam hal ini peneliti melakukan analisis dari implementasi kebijakan menurut Purwanto (2015) dimana ada tujuh indikator yang dapat digunakan untuk melihat kinerja implementasi kebijakan yaitu: Akses, Cakupan, Frekuensi, Bias, Ketepatan layanan, Akuntabilitas dan Kesesuaian program dengan kebutuhan. Metode yang digunakan yakni metode penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan dengan wawancara, observasi, dokumentasi dan triangulasi/gabungan. Hasil penelitian menunjukkan dari tujuh indikator kinerja implementasi, Balai Penyuluh Pertanian Kecamatan Pakisjaya sudah menjalankan program kartu tani dengan cukup baik. Hal itu bisa dilihat dari pendistribusian pupuk bersubsidi sudah merata hampir mencapai 100%, walaupun pendistribusian kartu tani belum 100% dikarenakan harus melewati birokrasi yang begitu rumit. Namun itu tidak menjadi penghalang, proses distribusi pupuk bersubsidi masih bisa dilakukan karena petani sudah terdaftar di RDKK.